DAMPAK PENERAPAN PSAK 24 (REVISI 2010), FAS 158 DAN ED PSAK 24 REVISI 2013 IMBALAN PASKAKERJA PROGRAM IMBALAN PASTI - GERRY TJANDRA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This research of implementation impact analysis to financial statements for post-employment benefit for defined benefit plans based on PSAK and FAS which implemented by Corporate Accountant, also implementation impact of Exposure Draft PSAK 24 Revised 2013 at PT HBS. This research was performed thru literature study, especially PSAK, FAS and ED PSAK. Research result based on independent actuary report in accordance with PSAK 24 (Revised 2010) and FAS 158 showed no difference calculation results on present value of defined benefit obligation and fair value of plan asset. Implementation of PSAK 24 (Revised 2010) with corridor approach method provided a lower of post-employment benefit for defined benefit plans liability but without corridor approach method provided increase of net liability and recognized all actuarial losses in other comprehensive income by decreased of 1.49 percent. Implementation of ED PSAK 24 Revised 2013 provided increase of net liability, decrease other comprehensive income, total equity and post-employment benefit expenses.